The Strategy of Teaching Writing in PTMT and BDR at SMAN 3 Kediri - Ike Mia Nopita Sari (STKIP PGRI Tulungagung, 2023)
The implementation of education during the new normal period of COVID-19 have regulated through the government regulation SKB-4. Government regulations encourage writing teaching strategies using PTMT and learning methods from home. This study uses qualitative research methods, this research have conducted based on the phenomenon of online and offline learning. Data collected through observations and interviews. Observations and interviews have shown that the teacher's role in face-to-face learning and learning from home is as a reviewer of learning materials, counselor regarding materials and obstacles faced by students, controller of learning and learning, and motivator. There are classroom management, chair arrangements, teacher body language, and the use of Google Classroom as a form of strategy in teaching writing. The combination of the pandemic RPP and K13 RPP as a guide in teaching. The learning model used has called the PTMT learning model and learning from home, which, combines several hybrid-learning models, blended learning and flipped learning. Teaching writing uses instant writing and contextual writing.